Penguatan Pendidikan Seksual pada Anak dalam Upaya Pencegahan Terjadinya Kekerasan Seksual Anak - Ikhwa Sasmitha; Berlianti Berlianti (Yayasan Literasi Sains Indonesia, 2023)
Cases of sexual violence against children are increasingly worrying. This should be an important concern that must be addressed immediately. One of the efforts that can be made in order to prevent the occurrence of sexual crimes against children is to provide reinforcement of sexual education for children and get rid of the taboo impression on this issue. This service activity was carried out using a comprehensive mentoring method for the children of the Damai Village of Binjai City through the socialization of the importance of sexual education in children in the form of delivering sexual education material that is suitable for children aged 6 to 9 years. The Intervention Program used in this Practicum activity is an Intervention with the Community Development method in which the implementation stages consist of; Engagement, Intake, Contract, Assessment, Planning, Intervention, Evaluation and Termination. The final output achieved from this activity is an increase in children's knowledge about sexual education and their skills in protecting themselves from situations that have the potential to lead to acts of sexual crime, so that they are able to interact socially properly and according to the norms in their social environment.